Studi Historis Tentang Dampak Sosial Konflik Komunal Di Kota Sambas Pada Tahun 1999 Terhadap Kehidupan Masyarakat Etnis Madura - Wardina, Yastrid Salwa; Firmansyah, Andang; Putri, Astrini Eka (STKIP Singkawang, 2006)
This research examines the social impact experienced by the Madurese community during the communal conflict in Sambas in 1999, focusing on the origins of the conflict, the evacuation process, relocation, dan the life of the Madurese community post-displacement. This research aims to examine the widespread impact of a communal conflict so that it can affect the conditions of the ethnic groups involved in it. This research uses the historical writing method with stages of topic selection, source collection, source critisim, interpretation, dan historiography. The results of this study indicate that the stigmatization of an ethnic group can ignite prolonged conflicts and attacks. Although this communal conflict highlights the violence between the Malay and Madurese ethcnic groups. However, there is intervention from the Dayak ethnic group who are on the side of the Malay ethnic groups. The efforts taken by the government and security forces have not been sufficient to stop the conflict from spreading to areas with low conflict intensity, such as the city of Sambas. As a result, there was a wave exodus of the Madurese ethnic group to the Pontianak area as a temporary refuge. This conflict also involved security forces who were spesifically brought in from oter regions due to the difficult conditions to handle. The conflict that occurred also forced the property and land belonging to the Madurese ethnic group to be sold at very low prices. The Madurese ethnic group also faced with various choices and start a new life by trying different jobs.